RESPONSIBLE WATER MANAGEMENT – INTERNATIONAL AND NATIONAL LEGAL AND STRATEGIC FRAMEWORK - Dokmanović, Mirjana (Glasnik Advokatske komore Vojvodine, 2022)
The subject of this article is the international legal and political framework on right to water and relevant regulations in the Republic of Serbia. The focus is on the state’s responsibilities for water management in accordance with the common good. The starting point is the argument that access to water is a human right, and that water can only be managed by the state and solely in the common interest. The first section discusses the risks of marketisation, privatisation and commodification of water upon the realization of the right to water rights and the protection of this vital natural and strategic resource. The second part sums up the activities of the United Nations regarding the recognition of right to water as a basic human right and the obligations of states with this respect. The third section analyzes the normative and strategic framework of the Republic of Serbia in this area from the perspective of the right to water and responsible water management. The analysis indicates deficiencies in compliance with international human rights standards and the risks current regulation can produce on the population, water resources and the society. Effective instruments for protecting water from pollution are not envisioned, as well as from its commification and marketing. The privatisation of waters and public enterprises in this area jeopardises the state’s sovereignty over its natural resources. The article aims to stress the importance of establishing a national regulation that will ensure sovereign and responsible management of water resources and protection of the right to water.